China : Country Water Resources Assistance Strategy - World Bank (Washington, DC, 2013)
China has very serious water problems despite substantial economic development achievements, strong technical expertise, and political stability. But in terms of its potential and the critical pressing needs for water resources management, China could do much better in managing its water resources. The World Bank's assistance to China in water resources development and management in the past has tended to be reactive and downstream in the project cycle. However, this approach has significantly limited the potential benefits of Bank assistance to China which a more upstream approach, based on a strategic partnership, could provide. The overall strategic objective is to improve water resources management. This strategy paper identifies China's principal water resource challenges, what China is already doing, and how the Bank can assist in the future. The large size of the Bank's water portfolio and the urgency of the problems, demand a strategic framework for the Bank's support to China. In 2002, the Bank and the Chinese Government are cooperating on the evaluation of the last, and preparation of the new, country assistance strategy. In October 2002, China promulgated a new water law, has recently prepared a new five-year plan, and is updating the master plans for the major river basins. The Bank hopes it can assist China in improving its water resources management, and accelerate implementation of reforms through a shared Country Water Resources Assistance Strategy (CWRAS).